Evaluation of the circulatory levels of heat shock protein 60 levels in periodontitis and cardiovascular disease patients - Rakshit K Dalal; Manpreet Kaur; Komal Khatri; Foram Patel; Heena Shaikh; Arifa Bakerywala (Wolters Kluwer Medknow Publications, 2024)
Introduction: HSP is arguably the most thoroughly studied self-antigens connected to Cardio Vascular Diseases (CVD) and periodontal disease. Hence, the major goal of this analysis was to determine the amount of HSP60 in patients' Chronic Periodontitis (CP) patients' serum. Materials and Methods: The current investigation involved 100 patients in all. Based on the patients' periodontal and cardiovascular health, the patients were divided. The patients were made aware that this research had no direct bearing on disease treatment or cure. Results: In contrast to periodontal disease, which had a mean serum HSP60 of 59.94 ng/dl, CVD had a mean serum HSP60 of 85.98 ng/dl. When compared to periodontal disease, the CVD increased significantly (P < 0.05, 0.03). Discussion and Conclusion: We emphasize the function of HSP60 in the pathophysiology of individuals with chronic periodontitis based on the findings of the current investigation. Serum HSP60 concentrations can serve as a biomarker for periodontal inflammation. More longitudinal and interventional research with a larger sample size is required to validate the present findings. In periodontal therapies, targeting HSP60 may enhance results.